Rekonstruksi Hadanah dengan Konsep Shared Parenting di Pengadilan Agama - Fuji Sunu, Handika; Pagar; Adly, M. Amar (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to introduce the concept of shared parenting as a solution to child custody disputes in religious courts. This research is a normative legal research, by analyzing the decision of Tarempa Religious Court Number 27/Pdt.G/2023/PA.Trp, the decision of Tarakan Religious Court Number 408/Pdt.G/2019/PA. Tar, and decision of Syar'iyah Kualasimpang Court Number 50/Pdt.G/2021/MS.Ksg. The results of this study show that the concept of shared parenting is one of the right choices to resolve child custody cases, this pattern is taken to break up situations when both parents fight each other for the right to hadanah. With this concept of co-parenting, it is hoped that after divorce, the relationship between parents and children will continue to be good and harmonious. The implementation of the concept of shared parenting in disputes in religious courts can be found in two products, namely rulings and peace deeds. The peace deed is also in the form of a ruling, but more specifically related to the legitimacy of the peace agreement that occurs in the mediation process, both within the court and outside the court.